2016
DOI: 10.1051/matecconf/20168003005
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of wrinkling and springback in sheet metal forming

Abstract: Abstract. The finite element simulation is currently a powerful tool to optimize forming processes in order to produce defect-free products. Wrinkling and springback are main geometrical defects arising in sheet metal forming. Nevertheless, the prediction of such defects requires accurate numerical models. This study presents the experimental and numerical analysis of a rail with high tendency to develop both wrinkling (top surface of geometry) and springback (flange). The punch force evolution and the final g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 30 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…In this study, two finite element codes are used to perform the BM2. One code is AutoForm (R6, AutoForm Engineering GmbH, Wilen bei Wollerau, Switzerland) [9], whose results will be labeled as AF-UP, and the other code is DD3IMP (v1.8, CEMMPRE, Coimbra, Portugal) [1,10], whose results are labeled as DD3-UC.…”
Section: Finite Element Methods Codes and Numerical Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, two finite element codes are used to perform the BM2. One code is AutoForm (R6, AutoForm Engineering GmbH, Wilen bei Wollerau, Switzerland) [9], whose results will be labeled as AF-UP, and the other code is DD3IMP (v1.8, CEMMPRE, Coimbra, Portugal) [1,10], whose results are labeled as DD3-UC.…”
Section: Finite Element Methods Codes and Numerical Modelsmentioning
confidence: 99%
“…In modern manufacturing industries, sheet metal-forming processes are commonly used to produce complex parts. The major concerns of the automotive industry are environmental protection (requiring low fuel consumption and low exhaust emissions) and the safety specifications [1]. Therefore, newer materials or solutions are required to reduce the weight of the vehicle body structures and closures, such as aluminum alloys and high-strength steels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the parameter with the most substantial influence was blank holder force with the number is 56.98%, the punch radius was 30.12%, and the die radius was 12.90%. p-ISSN: 1410-2331 e-ISSN: 2460-1217 Numerical experiments and analysis of rail shapes with a high tendency to form a wrinkle on surface of flange has been conducted by [7]. The formation process consists of three phases.…”
Section: Materials Thickness Ratio (T R ) and 2 Drawing Ratio (M)mentioning
confidence: 99%
“…Deep drawing is one of the most widely used SMF processes for producing cylindrical cup and flange cup cylinder components in a high level of accuracy and quality. Cylindrical cup shapes and cylindrical flange cups with deep drawing processes are widely used for the production of major components in the automotive, household, and electronic industries [4,5,6,7]. In the deep drawing process, a sheet metal blank is drawn over a die cavity using a shaped punch.…”
Section: Introductionmentioning
confidence: 99%